Influence of temsirolimus on antidiabetic effect of sitagliptin in experimental animal - Jamal, Roohi; K Suresh, D.; S Khalid, Md (International Journal of Pharmacology and Toxicology, 2018)
The present study was carried out to evaluate the drug interaction between an antihyperglycemic agent and anticancerous drug,In healthy and Dexamethasone induced diabetic rats. The blood samples were collected up to 24 h and blood glucose level was estimated. In healthy albino rats Pretreatment with Temsirolimus (6.75 mg/kg for seven days) has significantly altered the onset of hypoglycemia (15.50+1.47 to21.40Â±.54), p< 0.001 at the 2nd hour significantly enhanced the peak hypoglycemia (29.70+.60 %) before treatment to (44.47+1.21 %) after treatment(p<0.001) at 4th hour (i.e. 18.71Â±.38 to 20.43Â±.89, p<0.001 induced by Sitagliptin. Whereas in Dexamethasone treated rats, pretreatment with Temsirolimus (6.75 mg/kg) for 7 days has decreased the onset of hypoglycemia, significantly enhanced the peak hypoglycemia (24.13+.6417%) before treatment to (45.62+2.845 %) after treatment(P<.001) at the 8th hour. This study indicates that therapeutic drug monitoring has been required for therapeutic doses of temsirolimus and antidiabetic drugs when used concomitantly.HighlightsÂ 1)Â Â Â Â Â Influence of Temsirolimus on hypoglycemic activity of Sitagliptin in healthy rats.2)Â Â Â Â Â Influence of Temsirolimus on hypoglycemic activity of Sitagliptin in Dexamethasone induced hyperglycemic rats.3)Â Â Â Â Â To suggest the alteration in the dose and frequency of administration of Oral antidiabetic agents when they are used along with Temsirolimus.AbbreviationsÂ P.o.- per os â€˜by mouthâ€™, DM-Diabetes mellitus,GOD-Glucose oxidase (GOD), POD- Peroxidase (POD).Â